Anatomic stemless shoulder arthroplasty and related outcomes: a systematic review. Issue 1 (December 2016) - Hawi, Nael; Tauber, Mark; Messina, Michael; Habermeyer, Peter; Martetschläger, Frank
Abstract Background The latest generation of shoulder arthroplasty includes canal-sparing respectively stemless designs that have been developed to allow restoration of the glenohumeral center of rotation independently from the shaft, and to avoid stem-related complications. The stemless prosthesis design has also recently been introduced for use in reverse arthroplasty systems. Methods We systematically reviewed the literature for studies of currently available canal-sparing respectively stemless shoulder arthroplasty systems. From the identified series, we recorded the indications, outcome measures, and humeral-sided complications. Results We identified 11 studies of canal-sparing respectively stemless anatomic shoulder arthroplasty implants, published between 2010 and 2016. These studies included 929 cases, and had a mean follow-up of 26 months (range, 6 to 72 months). The rates of humeral component-related complications ranged between 0 and 7.9 %. The studies reported only a few isolated cases of complications of the humeral component. Some arthroplasty systems are associated with radiological changes, but without any clinical relevance. Conclusions All of the published studies of canal-sparing respectively stemless shoulder arthroplasty reported promising clinical and radiological outcomes in short to midterm follow-up. Long-term studies are needed to demonstrate the long-term value of these kind of implants.